Analisis Pengaruh Produk Domestik Regional Bruto (PDRB), Upah Minimum Regional (UMR) dan Tingkat Pengangguran Terbuka (TPT) Terhadap Kesejahteraan Dalam Perspektif Ekonomi Islam di Provinsi Sumatera Utara - Siregar, Tarmiji Hamid; Lubis, Fauzi Arif; Inayah, Nurul (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This study aims to determine the influence of PDRB, UMR and TPT on people's welfare (HDI) in North Sumatra Province for the 2017-2021 period. This research is a type of quantitative research that is associative in nature with a sample of 135 data from 27 districts/cities in North Sumatra Province which were collected through documentation from BPS. Data analysis technique using multiple linear regression analysis. The results of the study show: (1) PDRB partially has a positive and significant effect on people's welfare; (2) Partial UMR has no significant effect on the welfare of the community; (3) TPT partially has a positive and significant effect on people's welfare; and (4) PDRB, UMR and TPT jointly (simultaneously) have a significant effect on people's welfare in North Sumatra Province during the 2017-2021 period. The magnitude of the influence of the PDRB, UMR and TPT variables simultaneously on community welfare is 17.6% and the remaining 82.4% is explained by other variables besides the variables proposed in this study.